Quantitative measurement of cartilage volume is possible using two-dimensional magnetic resonance imaging data sets. Issue 7 (July 2018) - Schaefer, L.F.; Nikac, V.; Lynch, J.A.; Duryea, J.
Summary: Purpose: 3D Magnetic resonance imaging (MRI) scans are generally used for quantitative cartilage measurements in knee osteoarthritis. However, a great deal of MRI data is from 2D scans, often thought to be unsuitable for quantitative cartilage assessment. The goal of our study was to demonstrate that mLACS, a modified version of the Local Area Cartilage Segmentation (LACS) method, could be used to measure cartilage volume on 2D MRI images. Methods: We studied 301 randomly selected subjects from the OA Biomarkers Consortium FNIH Study, a nested case-control study within the Osteoarthritis Initiative (OAI). The study comprised four subgroups based on radiographic and pain progression. We compared mLACS applied to 2D TSE scans to LACS on 3D DESS data. The Pearson's correlation coefficient was used to establish agreement between LACS and mLACS, standardized response means (SRMs) for responsiveness, and intra-class correlation coefficients (ICCs) to measure reader precision. Logistic regression in a case/control analysis was used to compare the clinical validity between the two methods. Results: We found R 2  = 0.76 for the correlation between LACS and mLACs. For LACS, the responsiveness was SRM = 0.49 compared to 0.39 for mLACS. The odds ratios (OR) for the primary case/control analyses were 1.62 for LACS and 1.78 for mLACS. The intra and inter reader reproducibility values for mLACS were ICC = 0.90 and 0.86, respectively. Conclusion: This study has demonstrated that a reproducible, responsive, and clinically valid quantitative measurement of cartilage volume can be made using 2D TSE scans with a modest loss of responsiveness compared to 3D scans.